Roles, Reestructuración De Roles y Afrontamiento en Familias Victimas Del Conflicto Armado en Colombia Que Perdieron a Uno De Sus Padres (2019)
The following research seeks to expose the constructed understanding of past roles and their restructuring as well as the coping strategies used by the victims of the armed conflict in the country that suffered the loss of either their father or mother. The research design used is qualitative and narrative. The technique used to collect the information was a semi-structured interview composed of questions related to the different categories that were previously established according to the needs of the research. According to the information obtained it is possible to identify the changes in terms of roles generated by the violence and the different strategies used to cope with the situations experienced and present in those victims of the conflict